Characterization and annotation of oxidized glycerophosphocholines for non-targeted metabolomics with LC-QTOF-MS data - Gil de la Fuente, Alberto; Traldi, Federico; Siroka, Jitka; Kretowski, Adam; Ciborowski, Michal; Otero, Abraham; Barbas, Coral; Godzien, Joanna (Analytica chimica acta, 2018)
The biological role of oxidized glycerophosphocholines (oxPCs) is a current topic of research importantly contributing to the understanding of health and disease. Global non-targeted metabolomics offers an interesting approach to expand current knowledge and link oxPCs to new biological functions. Although this strategy is successful, it also has some limitations which are clearly noticeable during the identification process. For this reason, clear rules related to the identification of each group of metabolites are needed. This work attempts to provide the reader with a guideline for the recognition and annotation of oxidation among phosphocholines (PCs). Using several chromatographic characteristics and spectral information from tandem mass spectrometry, rapid and reliable annotation of long and short chain oxPCs can be performed. Some of this knowledge has been implemented in the publicly available annotation tool 'CEU Mass Mediator' (CMM) for semi-automated assignment of oxidation. Additionally, this tool was supplemented with accurate monoisotopic masses of oxPCs, expanding current information in other databases. Moreover, the characterization of oxidization products of PC(16:0/20:4) known as PAPC has been performed, providing a list of accurate mass product ions and neutral losses.
Keywords: Databases, Factual; chromatografie kapalinová; databáze faktografické; metabolomika; Humans; Molecular Structure; Non-targeted metabolomics; Annotation; Chromatography, Liquid; Mass Spectrometry; Oxidized glycerophosphocholines; fosfatidylcholiny; Metabolomics; diabetes mellitus 2. typu; hmotnostní spektrometrie; Phosphatidylcholines; oxidace-redukce; oxPAPC; Diabetes Mellitus, Type 2; lidé; LC-ESI-QTOF; Identification; Oxidation-Reduction; molekulární struktura